2015
DOI: 10.1007/s11948-015-9659-8
|View full text |Cite
|
Sign up to set email alerts
|

The Three Rs of Animal Research: What they Mean for the Institutional Animal Care and Use Committee and Why

Abstract: The Institutional Animal Care and Use Committee (IACUC) is entrusted with assessing the ethics of proposed projects prior to approval of animal research. The role of the IACUC is detailed in legislation and binding rules, which are in turn inspired by the Three Rs: the principles of Replacement, Reduction, and Refinement. However, these principles are poorly defined. Although this provides the IACUC leeway in assessing a proposed project, it also affords little guidance. Our goal is to provide procedural and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…Also, there was very little to no information provided on why particular data were not included in analyses or adverse events encountered during experiments. Studies also did not explicitly address potential implications for the “3Rs” (replacement, reduction, and refinement; Curzer et al., ) on the use of animals in research. Although this is a criterion in the ARRIVE guidelines, it is not common for animal studies to include this as part of their reporting.…”
Section: Resultsmentioning
confidence: 99%
“…Also, there was very little to no information provided on why particular data were not included in analyses or adverse events encountered during experiments. Studies also did not explicitly address potential implications for the “3Rs” (replacement, reduction, and refinement; Curzer et al., ) on the use of animals in research. Although this is a criterion in the ARRIVE guidelines, it is not common for animal studies to include this as part of their reporting.…”
Section: Resultsmentioning
confidence: 99%
“…This was also confirmed later for a large animal model with sheep by O’Brien et al [97]. Therefore the inclusion of a control group of animals without surgical treatment seemed not to be justified when the study protocol was performed also in terms of animal welfare (http://eur-lex.europa.eu, European directives on the protection of animals used for scientific purposes, DIRECTIVE 2010/63/EU, visited July 25th 2016 and [98]).…”
Section: Discussionmentioning
confidence: 96%
“…In vivo studies were performed on age matched adult male mice, unless otherwise indicated. All experiments were approved by the University of Pittsburgh IACUC ( 19 ).…”
Section: Methodsmentioning
confidence: 99%